Telecare and Elderly Mortality: Evidence from Italian Municipalities - Nicola Matteucci; Matteo Picchio; Raffaella Santolini; Rostand Arland Yebetchou Tchounkeu (Global Labor Organization (GLO), 2025)
The growing ageing of the population in developed economies has necessitated the progressive use of advanced information and communication technologies (ICTs) for the home care of elderly individuals. The effect of these technologies on elderly health outcomes remains an open issue. In this study, we analyze the impact of telecare on the mortality rate of elderly people in Italy using data at the municipal level and a doubly robust difference-in-differences design. Our results show that telecare services significantly reduced the mortality rate of the elderly aged 65 and over by 1.7 individuals per 1,000 inhabitants. This effect was sizeable, since it was a 4% decrease in the elderly mortality rate relatively to the average elderly mortality rate in the treated municipalities. The reduction in the elderly mortality rate was greater in municipalities with a large proportion of childless elderly people, suggesting that telecare may be particularly useful for the elderly who find it more difficult to rely on strong family ties. Moreover, it was stronger in small municipalities, indicating that telecare may be more effective where there is a greater need to compensate for a lower level of traditional social and health care services.
Keywords: I10; I18; 330; telecare; elderly; health; mortality rate; municipalities